Net ecosystem production and organic carbon balance of U.S. East Coast estuaries: A synthesis approach. Issue 1 (27th January 2015) - Herrmann, Maria; Najjar, Raymond G.; Kemp, W. Michael; Alexander, Richard B.; Boyer, Elizabeth W.; Cai, Wei‐Jun; Griffith, Peter C.; Kroeger, Kevin D.; McCallister, S. Leigh; Smith, Richard A.
Abstract Net ecosystem production (NEP) and the overall organic carbon budget for the estuaries along the East Coast of the United States are estimated. We focus on the open estuarine waters, excluding the fringing wetlands. We developed empirical models relating NEP to loading ratios of dissolved inorganic nitrogen to total organic carbon, and carbon burial in the sediment to estuarine water residence time and total nitrogen input across the landward boundary. Output from a data‐constrained water quality model was used to estimate inputs of total nitrogen and organic carbon to the estuaries across the landward boundary, including fluvial and tidal‐wetland sources. Organic carbon export from the estuaries to the continental shelf was computed by difference, assuming steady state. Uncertainties in the budget were estimated by allowing uncertainties in the supporting model relations. Collectively, U.S. East Coast estuaries are net heterotrophic, with the area‐integrated NEP of −1.5 (−2.8, −1.0) Tg C yr−1 (best estimate and 95% confidence interval) and area‐normalized NEP of −3.2 (−6.1, −2.3) mol C m−2 yr−1. East Coast estuaries serve as a source of organic carbon to the shelf, exporting 3.4 (2.0, 4.3) Tg C yr−1 or 7.6 (4.4, 9.5) mol C m−2 yr−1. Organic carbon inputs from fluvial and tidal‐wetland sources for the region are estimated at 5.4 (4.6, 6.5) Tg C yr−1 or 12 (10, 14) mol C m−2 yr−1 and carbon burial in the open estuarine waters at 0.50 (0.33, 0.78) Tg C yr−1 or 1.1 (0.73, 1.7) mol C m−2 yr−1. Our results highlight the importance of estuarine systems in the overall coastal budget of organic carbon, suggesting that in the aggregate, U.S. East Coast estuaries assimilate (via respiration and burial) ~40% of organic carbon inputs from fluvial and tidal‐wetland sources and allow ~60% to be exported to the shelf.